Cistatinas de cana-de-açúcar: produção recombinante em vacúolos de cana-de-açúcar transgênica (e outros sistemas de expressão em plantas) e estudos de interação com uma pseudo protease do coleóptero Sphenophorus levis - Shibao, Priscila Yumi Tanaka (Universidade Federal de São Carlos, 2021)
Sphenophorus levis (Curculionidae: Coleoptera) is one of the major pests of sugarcane crop in Brazil and presents cysteine proteases as main digestive enzymes. In this project, we report the characterization of Sl-CathL-CS, a variant of the main digestive cathepsin (Sl-CathL) of the insect S. levis that presents a serine residue instead of a cysteine in the catalytic site at position 138. In addition, a mutant enzyme, in which serine 138 was replaced by a cysteine residue was produced and named Sl-CathL-mutSC. Sl-CathL-CS did not show proteolytic capacity, but Sl-CathL-mutSC was able to hydrolyze milk proteins and the substrate Z-Phe-Arg-AMC (Vmax = 1017.6 ± 135.55 and Km = 10.766 mM). This mutant was inhibited by E-64 (Ki = 38.52 ± 1.2 μM), but not by PMSF, which is an inhibitor of serine proteases, and the static docking showed the difference of the active site of the two proteins. Interaction assay between them and the cystatin CaneCPI-1 revealed that Sl-CathL-CS has greater interaction with this cystatin, indicating that the protein can assist in the insect digestive process by interacting with the plant cystatins thus allowing the true proteases to work. Considering the importance of the cystatin/cysteine proteases interaction, Laboratory of Molecular Biology has dedicated itself to the study of sugarcane cystatins, being responsible for the identification and characterization of six of them (CaneCPI-1 to CaneCPI-6). Among them, CaneCPI-5 presented high inhibitory capability against Sl-CathL, which is the main digestive enzyme of the insect, besides inhibiting other cysteine cathepsins. Interestingly, this cystatin can protect tooth enamel against acid erosion and cavities. For this reason, there is a need to upscale its production to fulfill potential industrial demand. In this work, CaneCPI-5 was produced in a plant-based system by cell lysates (cell-free systems) of Nicotiana tabacum cv Bright Yellow cells (BY-2 cells), transient expression in leaves of Nicotiana benthamiana and stable expression in BY-2 cells. It was possible to obtain 25 μg of purified protein per gram of infiltrated leaf and the protein showed similar inhibition (Ki = 10 nM) to that of CaneCPI-5 produced in bacteria. CaneCPI-5 was also produced in transgenic sugarcane vacuoles and was purified from its juice, yielding 200 ug per mL, which, in the field, would allow the production of up to 15.3 kg of protein per hectare of sugarcane. The transgenic sugarcane events had their resistance against the attack of S. levis larvae assessed, however the transgenic clones failed to express the protein in the juice after propagation in the greenhouse, which may have occurred by gene silencing. This may have been responsible for them not showing increased resistance.
Sugarcane cystatins: recombinant expression in vacuoles of transgenic sugarcane (and other plant-based expression systems) and interaction with a pseudo protease from Sphenophorus levis
Keywords: Cana-de-açúcar transgênica; Canacistatina; Pseudo cisteíno protease; Sphenophorus levis; Molecular farming; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR